Pengaruh Model Pembelajaran PJBL dan TTW terhadap Kemampuan Menulis Teks Berita di SMPN 9 Bontang: The Influence of PJBL and TTW Learning Models on News Text Writing Skills at SMPN 9 Bontang - Lilyn Indriyawati; Masrur Yahya; Dwi Nugroho Hidayanto; Yusak Hudiyono; Azainil Azainil; Bahri Arifin (ITScience (Information Technology and Science), 2025)
Writing ability is one of the basic competencies in Indonesian language learning that students must master. This skill is important as part of the learning process and as a means of developing thought patterns, creativity, and the ability to convey ideas logically and systematically. Among the various forms of text taught at the junior high school level, news text requires students to understand the structure of presenting factual information, use objective language, and follow journalistic rules. This study aims to determine the effect of the PjBL and TTW learning models on news text writing skills. This research is quantitative with an experimental method. The population in this study were all 96 seventh-grade students of SMPN 9 Bontang in the 2023/2024 academic year. The sample selection in this study used a purposive sampling technique and selected 64 students from class VII-B and class VII-C. Data analysis techniques used were the Kolmogorov-Smirnov test (normality), the Bartlett test (homogeneity) and for hypothesis testing using the t-test. Based on the results of data analysis techniques, it is known that the percentage of students' success with the implementation of PjBL in achieving the criteria for learning objectives is 54% and students with the implementation of TTW is only 46%. There is an influence of the PjBL and TTW learning models on the ability to write news texts.